2021
DOI: 10.1007/s11011-021-00873-7
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1224 downregulation inhibits OGD/R-induced hippocampal neuron apoptosis through targeting Ku protein

Abstract: Ischemic cerebrovascular disease is the main cause of disability due to stroke. This study aimed to investigate the function of miR-1224 in OGD/R-induced hippocampal neuron apoptosis, as well as the regulatory mechanism of miR-1224 in ischemic cerebrovascular disease. The oxygen-glucose deprivation/reperfusion (OGD/R) model of primary mouse hippocampal neurons was established. RT-qPCR detected miR-1224, Ku70 and Ku86 levels. Western blotting was applied to measure the expression of Ku70/86 and apoptosis relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Previous studies showed that apoptosis was implicated in the pathophysiology of both central and peripheral nerve injury (Eldadah and Faden, 2000;Jia et al, 2020), and our previous work demonstrated that neuronal apoptosis was also induced in LSRA and might be a key factor restricting the surgical repair effects (Jiang et al, 2014;Zhou et al, 2019c). Specifically, among the predicted miRNAs, rno-miR-1224 and rno-miR-326-5p have been reported to be involved in neuronal apoptosis (Huang et al, 2021;Wan and Xiao, 2022), suggesting that they are likely to be involved in LSRA by regulating neuronal apoptosis. Moreover, we also identified differentially expressed mRNAs targeted by rno-miR-1224 and rno-miR-326-5p, and KEGG pathway analysis revealed that these mRNAs were also significantly enriched apoptosis-associated signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that apoptosis was implicated in the pathophysiology of both central and peripheral nerve injury (Eldadah and Faden, 2000;Jia et al, 2020), and our previous work demonstrated that neuronal apoptosis was also induced in LSRA and might be a key factor restricting the surgical repair effects (Jiang et al, 2014;Zhou et al, 2019c). Specifically, among the predicted miRNAs, rno-miR-1224 and rno-miR-326-5p have been reported to be involved in neuronal apoptosis (Huang et al, 2021;Wan and Xiao, 2022), suggesting that they are likely to be involved in LSRA by regulating neuronal apoptosis. Moreover, we also identified differentially expressed mRNAs targeted by rno-miR-1224 and rno-miR-326-5p, and KEGG pathway analysis revealed that these mRNAs were also significantly enriched apoptosis-associated signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Of the five miRNAs, rno-miR-1224 and rno-miR-326-5p were previously reported to be involved in neuronal apoptosis (Huang et al, 2021;Wan and Xiao, 2022), and our previous studies demonstrated that neuronal apoptosis might be a key physiological process in LSRA (Jiang et al, 2014;, Frontiers in Genetics frontiersin.org 2019c). To construct a circRNA/miRNA/mRNA network related to neuronal apoptosis, we further predicted targeted mRNAs of rno-miR-1224 and rno-miR-326-5p, and intersected them with differentially expressed mRNAs identified by RNA-seq.…”
Section: Construction Of the Circular Ribonucleic Acid/microrna/messe...mentioning
confidence: 96%
“…Overexpression of miR-1224 inhibits hepatocyte proliferation and promotes apoptosis, according to Roy et al [ 58 ]. A study by Wan and Xiao found that downregulating miR-1224 prevented neuronal apoptosis and mitochondrial damage caused by OGD/R [ 59 ]. We speculate that lncRNA NONRATT019701.2 and lncRNA XR_001838273.1 may have the potential to regulate the proliferation of microglia and glial cells.…”
Section: Discussionmentioning
confidence: 99%